Regional monetary integration in the member states of the Gulf Cooperation Council - Michael Sturm; Nikolaus Siegfried (European Central Bank (ECB), 2005)
The Gulf Cooperation Council (GCC) plans to introduce a single currency by 2010 in its six member states, Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and the UAE. This paper focuses on selected macroeconomic and institutional issues and key policy choices which are likely to arise during the process of monetary integration. The main findings are that (i) a supranational GCC monetary institution is required to conduct a single monetary and exchange rate policy geared to economic, monetary and financial conditions in the monetary union as a whole; (ii) GCC member states have already achieved a remarkable degree of monetary convergence, but fiscal convergence remains a challenge and needs to be supported by an appropriate fiscal policy framework; and (iii) there is currently a high degree of structural convergence, although this is expected to diminish in view of the process of diversification in GCC economies, which calls for adequate policy responses.
Keywords: 330; Währungsunion; Wirtschaftliche Konvergenz; Arabische Golf-Staaten